A dynamically coupled outfall plume-circulation model for effluent dispersion in Burrard Inlet, British Columbia. Issue 5 (1st September 2004) - Li, Sheng; Hodgins, Donald O
Abstract : A circulation-water quality model, coupled with an outfall plume model, has been developed, to predict three-dimensional circulation and effluent dispersion as functions of circulation forcing, ocean turbulent mixing, discharge rate and diffuser parameters. The coupled model was applied to the Lions Gate outfall discharging sewage into Burrard Inlet, British Columbia; in this case, the circulation was driven by the tides and density variations. The model results have good agreement with dye survey data and acoustic Doppler current profiler (ADCP) measurements from the inlet. Under typical oceanographic conditions for the area, the model predicts submerged plumes below 8 m depth at most times. Short-lived surfacing occurs for a few minutes at slack tide. The near-field trapping level and initial dilution are controlled by tidal flows through First Narrows and the effluent discharge rate. Key words : outfall, diffuser, numerical model, dispersion, circulation, dilution, plume, Burrard Inlet.